1999
DOI: 10.1097/00001756-199905140-00023
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet reduces spontaneous seizures and mossy fiber sprouting in the kainic acid model

Abstract: The high fat, low carbohydrate, low protein ketogenic diet (KD) has been used to control refractory epilepsy in children since 1920, although its mechanism of action is unknown. Previous animal studies have shown that the KD can increase acute seizure threshold, but the effect of the KD on the process of epileptogenesis has not been studied. We tested the effect of an experimental KD on epileptogenesis in adult rats using the kainic acid (KA) model. P54 rats underwent KA-induced status epilepticus, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 12 publications
2
71
0
Order By: Relevance
“…This was first demonstrated in 1999 by Muller-Schwarze et al [82], who found that rats fed a ketogenic diet had fewer and briefer spontaneous recurrent seizures after kainic acid-induced status epilepticus than did control animals. In a subsequent study it was found that early initiation of the diet is necessary to obtain this antiepileptogenic effect [83].…”
Section: Antiepileptogenic Activity Of the Ketogenic Dietmentioning
confidence: 85%
“…This was first demonstrated in 1999 by Muller-Schwarze et al [82], who found that rats fed a ketogenic diet had fewer and briefer spontaneous recurrent seizures after kainic acid-induced status epilepticus than did control animals. In a subsequent study it was found that early initiation of the diet is necessary to obtain this antiepileptogenic effect [83].…”
Section: Antiepileptogenic Activity Of the Ketogenic Dietmentioning
confidence: 85%
“…Muller-Schwartze et al (40) found that administration of the KD after kainic acid-induced SE reduced both spontaneous seizure frequency and mossy fiber sprouting. Likewise, Noh et al (41) found that the KD inhibited apoptosis after kainic acid-induced SE.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is accumulating evidence from studies in models of chronic epilepsy that the ketogenic diet has antiepileptogenic properties that extend beyond its anticonvulsant efficacy. Thus, in the rat kainic acid model of temporal lobe epilepsy, the development of spontaneous seizures was attenuated by the ketogenic diet and there was a reduction in the severity of the seizures that did occur (Muller-Schwarze et al, 1999;Stafstrom et al, 1999;Su et al, 2000). In addition, animals fed the diet have reduced hippocampal excitability and decreased supragranular mossy fiber sprouting in comparison with rats fed a normal diet.…”
Section: Epilepsymentioning
confidence: 97%